Health-care Professionals' Perception toward Medical Device Postmarket Surveillance Practices: A Cross-sectional Study in India - Shatrunajay Shukla; Bikash Ranjan Meher; Archana Mishra; Shubhang Arora; Vivekanandan Kalaiselvan; Rajeev Singh Raghuvanshi (Wolters Kluwer Medknow Publications, 2024)
A cross-sectional, web-based survey was conducted to assess the health-care professionals (HCPs)' perception toward existing medical device postmarket surveillance (PMS) practices in India. A total of 1756 responses (medical practitioners [19.8%], nurses [22.5%], pharmacists [21.4%], and biomedical engineers [13.8%]) were recorded and analyzed. About 71.2% of participants were aware about the ongoing PMS program, 87.5% were aware that medical devices are under regulation in India, and 83.3% were aware about who can report medical device adverse event (MDAE). About 56.3% of participants agreed that they take regular feedback from patients after using high-risk medical device. Majority of participants (69.4%) were aware about tools for reporting MDAE and the online reporting form is the most preferable tool among users. About 76.2% of participants were agreeing that reporting of MDAE is their professional/ethical responsibility. This study reveals that Indian HCPs show a good understanding of PMS practices and a positive perception toward MDAE reporting. However, underreporting still remains a challenge in India.